Efficiency of 123I-ioflupane SPECT as the marker of basal ganglia damage in acute methanol poisoning: 6-year prospective study - Kotikova, Katerina; Zogala, David; Ptacnik, Vaclav; Trnka, Jiri; Kupka, Karel; Vaneckova, Manuela; Seidl, Zdenek; Diblik, Pavel; Heissigerova, Jarmila; Navratil, Tomas; Komarc, Martin; Zak, Ivan; et al. (Clinical toxicology (Philadelphia, Pa.), 2021)
CONTEXT: Investigate whether 123I-ioflupane SPECT (DaT SPECT) has the potential as a marker of basal ganglia damage in acute methanol poisoning. METHODS: Prospective, single-centre, cohort study of patients with confirmed methanol poisoning was conducted. DaT SPECT was performed twice with semi-quantification using DaTQUANTTM and MRI-based volumetry was calculated. Specific binding ratios (SBR) of striatum, caudate nucleus, and putamen were correlated with laboratory parameters of outcome, volumetric data, and retinal nerve fibres layer (RNFL) thickness measurements. RESULTS: Forty-two patients (mean age 46.3 ± 4.2 years; 8 females), including 15 with MRI-detected putamen lesions (group I) and 27 patients with intact putamen (group II), underwent DaT SPECT. Volumetry was calculated in 35 of the patients assessed. SBR values for the left putamen correlated with putamen volume (r = 0.665; p < 0.001). Decreased bilateral SBR values were determined for the striatum and the putamen, but not for the nucleus caudate, in group I (p < 0.05). Significant correlation was observed between the SBR of the posterior putamen and arterial blood pH (r = 0.574; p < 0.001) and other toxicological parameters of severity of poisoning/outcome including serum lactate, glucose, and creatinine concentrations (p < 0.05). The SBR of the posterior putamen positively correlated with the global RNFL thickness (p < 0.05). ROC analysis demonstrated a significant discriminatory ability of SBR of the posterior putamen with AUC = 0.753 (95%CI 0.604-0.902; p = 0.007). The multivariate regression model demonstrated that arterial blood pH, age, and gender were the most significant factors associated with SBR of the posterior putamen. CONCLUSION: DaT SPECT demonstrates significant potential for the diagnosis of methanol-induced basal ganglia damage.
Keywords: radioizotopy jodu; Putamen; methanol; Male; longitudinální studie; Tomography, Emission-Computed, Single-Photon; magnetická rezonanční tomografie; bazální ganglia; Basal Ganglia Diseases; Radiopharmaceuticals; jednofotonová emisní výpočetní tomografie; Nortropanes; Adult; basal ganglia lesion; Prospective Studies; dospělí; mužské pohlaví; Neuroimaging; Methanol; Iodine Radioisotopes; neurozobrazování; toxic brain damage; putamen; radiofarmaka; lidé; Methanol poisoning; ženské pohlaví; Basal Ganglia; Humans; nortropany; Longitudinal Studies; 123I-ioflupane SPECT; putamen necrosis; Magnetic Resonance Imaging; MRI-volumetry; Female; nemoci bazálních ganglií; lidé středního věku; Middle Aged; prospektivní studie